If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(3x + 1) = 3x + -8x Reorder the terms: 7(1 + 3x) = 3x + -8x (1 * 7 + 3x * 7) = 3x + -8x (7 + 21x) = 3x + -8x Combine like terms: 3x + -8x = -5x 7 + 21x = -5x Solving 7 + 21x = -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 7 + 21x + 5x = -5x + 5x Combine like terms: 21x + 5x = 26x 7 + 26x = -5x + 5x Combine like terms: -5x + 5x = 0 7 + 26x = 0 Add '-7' to each side of the equation. 7 + -7 + 26x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 26x = 0 + -7 26x = 0 + -7 Combine like terms: 0 + -7 = -7 26x = -7 Divide each side by '26'. x = -0.2692307692 Simplifying x = -0.2692307692
| 0.02x+0.5=0.35x+1.2 | | 5x+1=-13x+15 | | 2z+96=15z-85z | | 21x^2=7x | | x^2+2i=0 | | an=5n-8 | | -9+90=9x-90 | | 5x-95=x | | -8y-2=-7y-7 | | 3-4x+6-7=42 | | lnx=0.85 | | x^2+12x=540 | | 4(x-3)+2x=10 | | 1+15=-4(4x-4) | | 7x+9y=3+9x | | 30x^2+273x-270=0 | | m+11/8=8 | | 1+15=4(4x-4) | | 15x-5=25x+3 | | 2(x-3)+10=18 | | -4(x+1)-14=16+2 | | x+7+4x-3=3x+x-2x+16 | | 5k-3/(-3) | | y=-(1/3)x | | y=7000x+b | | 5k-3/3 | | 5k-3/-33 | | y=7000x | | 2(3x+9)=29+35 | | 4b^3(2b^4-10b^3+3)= | | 10z-7=6 | | 7/2(2/3-5/4x)=3/10 |